Topiramate sprinkle is effective in the treatment of childhood epilepsy - Gunawan, Prastiya Indra; Suharso, Darto (Faculty of Medicine, Trisakti University, 2012)
BackgroundEpilepsy remains one of the most frequently occurring pediatric problems. Approximately 10-15% patients do not respond to conventional therapy. Topiramate as a novel antiepileptic drug has a broad spectrum activity, presumably indicative of multiple anti-seizure mechanisms. Previous studies of topiramate as adjunctive and monotherapy in adults have shown beneficial effects. The objective of this research was to evaluate the efficacy and tolerability of topiramate sprinkle monotherapy in pediatric epilepsy.MethodsThis experimental research was conducted in the Pediatric Neurology outpatient clinic department, Soetomo hospital, Surabaya, involving 18 consecutive subjects. Subjects meeting the inclusion criteria were treated with topiramate sprinkle adjusted dose. Seizure frequency and side effects were observed in weeks 1, 4, 8, 12, 16, 20 and 24, respectively. Electro encephalogram (EEG) and laboratory examinations were performed prior to and after 6 months of treatment. The t-test for related samples and McNemar test were utilized for statistical analysis. ResultsA total of 15 subjects completed the study. Topiramate-treated patients showed a statistically significant difference of seizure frequency reduction from 2.7 Â± 1.16 to 0.13 Â± 0.51 (p=0.000) with 93.7% patients being seizure free in 20 weeks. EEG recordings did not differ statistically in decrement of epileptiform activity in 20% subjects. About 7% subjects developed drowsiness and 33.3% subjects suffered from appetite suppression in the initial treatment. Laboratory results showed no abnormalities. ConclusionsThere was reduction of seizure frequency and no EEG recording alterations after topiramate sprinkle monotherapy. Topiramate as a monotherapy is highly effcicacious in childhood epilepsy.